Identification and isolation of antigen-specific cytotoxic T lymphocytes with an automated microraft sorting system. Issue 12 (17th November 2016) - Attayek, Peter J.; Hunsucker, Sally A.; Sims, Christopher E.; Allbritton, Nancy L.; Armistead, Paul M.
Abstract : The simultaneous measurement of T cell function with recovery of individual T cells would greatly facilitate characterizing antigen-specific responses both in vivo and in model systems. Abstract : The simultaneous measurement of T cell function with recovery of individual T cells would greatly facilitate characterizing antigen-specific responses both in vivo and in model systems. We have developed a microraft array methodology that automatically measures the ability of individual T cells to kill a population of target cells and viably sorts specific cells into a 96-well plate for expansion. A human T cell culture was generated against the influenza M1p antigen. Individual microrafts on a 70 × 70 array were loaded with on average 1 CD8 + cell from the culture and a population of M1p presenting target cells. Target cell killing, measured by fluorescence microscopy, was quantified in each microraft. The rates of target cell death among the individual CD8 + T cells varied greatly; however, individual T cells maintained their rates of cytotoxicity throughout the time course of the experiment enabling rapid identification of highly cytotoxic CD8 + T cells. Microrafts with highly active CD8 + T cells were individually transferred to wells of a 96-well plate, using a needle-release device coupled to the microscope. Three sorted T cells clonally expanded. All of these expressed high-avidity T cell receptors for M1p/HLA*02:01 tetramers, and 2 of the 3 receptors were sequenced. While this study investigated single T cell cytotoxicity rates against simple targets with subsequent cell sorting, future studies will involve measuring T cell mediated cytotoxicity in more complex cellular environments, enlarging the arrays to identify very rare antigen specific T cells, and measuring single cell CD4 + and CD8 + T cell proliferation.